OPPORTUNITIES AND CHALLENGES OF SOCIAL MEDIA USE IN MUNICIPALITIES IN LATVIA - Lase, Kate; Sloka, Biruta (University of Latvia, 2022)
The use of different kind of social media by local governments has gained relevance in recent years, however, along with many opportunities and successes, the use of social media by local governments has many challenges, barriers and issues which are not enough researched and discussed in academic research. Purpose of the study is to analyse benefits and challenges of social media use in municipalities in Latvia. Research methods used in preparation of the paper: recent scientific publication studies, analysis of social media of municipalities of Latvia, survey on social media use in municipalities in Latvia realized on April 2021. For data analysis there were used indicators of descriptive statistics: indicators of central tendency or location (arithmetic mean, mode, median, quartiles), indicators of variability (variance, standard deviation, standard error of mean), cross – tabulations, statistical tests of hypotheses and analysis of variance (ANOVA). The results show that most municipalities generally have positive views of their social media use but the real application of social media is not consistent in each municipality. Although majority of municipalities use at least two social media, the study found important challenges in terms of reginal development, digital skills, appropriate employees and social media content.
The research was supported by the NATIONAL RESEARCH PROGRAMME “LATVIAN HERITAGE AND FUTURE CHALLENGES FOR THE SUSTAINABILITY OF THE STATE” project “CHALLENGES FOR THE LATVIAN STATE AND SOCIETY AND THE SOLUTIONS IN INTERNATIONAL CONTEXT" (INTERFRAME-LV, Project No.VPP-IZM-2018/1-0005).
Keywords: digital skills; Facebook; municipalities; social media; social networks; Research Subject Categories::SOCIAL SCIENCES::Business and economics